Sweat in Skin Homeostasis and Dermatological Disorders in Athletes: Structural, Functional, and Clinical Perspectives - A Narrative Review - Jarowicz, Monika; Marczak, Zuzanna; Sito, Maksymilian; Jurkowski, Filip; Wójcik, Łukasz; Gawron, Natalia; Bojanowski, Hubert Tomasz; Dobracka, Aleksandra; Zachar, Kinga; Czmyr, Jędrzej (Journal of Education, Health and Sport, 2026)
Introduction and purpose. Sweat is essential for skin homeostasis. In physically active individuals, increased sweating supports protective skin functions but may also trigger dermatological conditions. This review summarizes current knowledge on sweat gland types, their functional diversity, and the role of sweat in skin homeostasis, dermatoses, and gland disorders. Material and method. A narrative review of the literature was conducted using PubMed and Google Scholar, including original articles and reviews on sweat gland physiology, sweat composition, and related dermatoses. Results. Secretions from eccrine, apocrine, and apoeccrine glands contain water, electrolytes, and bioactive molecules that contribute to epidermal barrier integrity and immune functions. In physically active individuals, increased sweating improves heat dissipation, enhances stratum corneum hydration, and facilitates the delivery of antimicrobial and immunomodulatory factors to the skin surface. However, prolonged moisture and friction may disrupt the skin barrier and promote microbial overgrowth, contributing to inflammatory, infectious, and exacerbate dermatoses. Sweat gland disorders, further illustrate the consequences of dysregulated sweating, leading to impaired thermoregulation, inflammation, discomfort, and reduced physical performance. Conclusions. Sweat has multifactorial effects on skin health, influenced by environmental and individual factors. Understanding sweat physiology and related disorders is essential for preventing and managing skin diseases.